2013
DOI: 10.1016/j.foodcont.2012.04.020
|View full text |Cite
|
Sign up to set email alerts
|

The application of the Appropriate Level of Protection (ALOP) and Food Safety Objective (FSO) concepts in food safety management, using Listeria monocytogenes in deli meats as a case study

Abstract: To establish a link between governmental food safety control and operational food safety management, the concepts of the Appropriate Level of Protection (ALOP) and the Food Safety Objective (FSO) have been suggested by international bodies as a means of making food safety control transparent and quantifiable. The purpose of this study was to investigate how the concepts of ALOP and FSO could be applied in practice. As a case study, the risk of severe listeriosis due to consumption of deli meat products in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Beside the original scientific result concerning an aseptic UHT dairy product line, the added value of this study was also the presentation of a methodology enabling to quantitatively evaluate the management options to control/reduce a risk. There are only few studies describing similar approaches, at least in the food safety or food spoilage fields (Crouch et al, 2009;Gkogka et al, 2013;Perez-Rodriguez et al, 2006;Tenenhaus-Aziza et al, 2014). Having a modular model structure, with each module covering different microbial pathways, helps in performing a logical risk analysis.…”
Section: Using a Qmea Model To Analyze The Risk Associated With An Asmentioning
confidence: 99%
“…Beside the original scientific result concerning an aseptic UHT dairy product line, the added value of this study was also the presentation of a methodology enabling to quantitatively evaluate the management options to control/reduce a risk. There are only few studies describing similar approaches, at least in the food safety or food spoilage fields (Crouch et al, 2009;Gkogka et al, 2013;Perez-Rodriguez et al, 2006;Tenenhaus-Aziza et al, 2014). Having a modular model structure, with each module covering different microbial pathways, helps in performing a logical risk analysis.…”
Section: Using a Qmea Model To Analyze The Risk Associated With An Asmentioning
confidence: 99%
“…In their analysis of Salmonella epidemiological data, Gkogka et al (2013b) considered that the number of under-reported cases was high (38 cases for 1 actual reported one) while for Listeria monocytogenes, they estimated that the figure was much lower (2 cases for 1 actual reported one) (Gkogka et al, 2013a). In the absence of solid values for C. botulinum, it was decided to adopt a fail-safe approach: the number of illness per million inhabitants was kept as calculated (Eq.…”
Section: Calculation Of Probability Of Illness Per Inhabitantmentioning
confidence: 99%
“…(11)) and not multiplied by a somewhat arbitrary factor. This is a fail-safe approach as the number of illness per million inhabitant might be used to recommend an ALOP on the assumptions that the current number of illnesses per million inhabitants is deemed acceptable (Gkogka et al, 2013a). By keeping the number of illness per million inhabitant low, we keep the ALOP value low as well.…”
Section: Calculation Of Probability Of Illness Per Inhabitantmentioning
confidence: 99%
See 2 more Smart Citations